2009
DOI: 10.15845/noril.v1i1.17
|View full text |Cite
|
Sign up to set email alerts
|

A New Conception of Information Literacy for the Digital Environment in Higher Education

Abstract: This paper outlines the author’s intellectual journey towards a deeper understanding of the nature of information literacy and how IL learning can be supported. This work was stimulated by a consultancy in one UK university to recommend an appropriate IL framework for use on their VLE. The journey described here considers relevant principles of learning, the place of student reflection in IL learning, what IL in HE should encompass, the importance of context in developing IL, and the influence of the digital e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 22 publications
0
17
0
2
Order By: Relevance
“…When comparing the contents related to each INFOLIT stage, it can be observed that the literature on this topic shows several models that try to frame the content of each stage from different viewpoints (ALA/ACRL, 2000a, 2000bANZIL and CAUL, 2004;Bruce, 2003;Bruce et al, 2006;Council of Australian University Librarians, 2001;Markless, 2009;Markless and Streatfield, 2007;SCONUL, 1999SCONUL, , 2011. Nonetheless, since it was first coined by Zurkowski (1974), the essential elements that make up information literacy have changed and the technologies supporting it have developed.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the contents related to each INFOLIT stage, it can be observed that the literature on this topic shows several models that try to frame the content of each stage from different viewpoints (ALA/ACRL, 2000a, 2000bANZIL and CAUL, 2004;Bruce, 2003;Bruce et al, 2006;Council of Australian University Librarians, 2001;Markless, 2009;Markless and Streatfield, 2007;SCONUL, 1999SCONUL, , 2011. Nonetheless, since it was first coined by Zurkowski (1974), the essential elements that make up information literacy have changed and the technologies supporting it have developed.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when information started to appear online, practice and research underwent transformations and changed in focus. Several authors have commented on the evolution of IL in the context of changes in information environments (Špiranec and Banek Zorica 2010;Markless 2009;Stoecklin 2012). M. Farkas (2011) has recognized three phases in the evolution of the concept: 1) library-focused user education, 2) internet-focused IL education, and 3) IL in the Web 2.0 era.…”
Section: Il and Its Evolutionmentioning
confidence: 99%
“…Bowler (2010) wrote that "keeping a search journal helps to make the evolution of thinking explicit" (p. 40). Without using the word "log" or "journal" or any analogous term, Markless (2009) promotes "activities that enable students to make their current information strategies and skills transparent so that they can be discussed and reflected upon as a basis for development" (p. 37). Writing professor Norgaard (2003Norgaard ( , 2004 wrote an influential pair of articles in which he urged collaboration between instructors of IL and composition.…”
Section: Pedagogy: Cognitivementioning
confidence: 99%